Surface Quality of Commercially Manufactured Particleboard Panels in Indonesia - Salim Hiziroglu; Yusuf Sudo Hadi; Dede Hermawan (Masyarakat Peneliti Kayu Indonesia, 2008)
This study is an attempt to evaluate surface roughness of commercially manufactured particleboard in Indonesia. Four different types of particleboard panels were used to measure their surface roughness on a stylus type of profilometer. Three roughness parameters, namely average roughness (Ra), mean peak-to-valley height (Rz), and maximum roughness (Rmax) were employed to quantify roughness of the samples. Panel type-D had the roughest surface characteristics with an average Ra value of 14.20 µm while panel type-A had the smoothest corresponding value of 6.13 µm. Panel types C and D had relatively rough surface as compared to surface of typical commercially manufactured particleboard panels due to having large particles on the surface layers. In further studies surface roughness of such samples could be investigated following a sequence of sanding process to improve their surface qualities.